Solid plexiform multicystic ameloblastoma in left mandibular body. Case report - González Rebattú, Mauricio (2018)
In 2017, World Health Organization described the ameloblastoma like a benign, locally invasive neoplasm , that consists in proliferation of odontogenic epithelium, which usually presents a folicular or plexiform pattern, and it is found inside a fibrous stroma. It presents slow development and affinity with woven osseus tissue, with high recurrence (60% -80%) if it is not well resected. Variants like uniquistic and desmoplastic have better prognostic than solid o multicyst. It represents the 1% of tumors of the jaw and the 11% of odontogenic tumors. The following case is a male patient, 43 years old which goes to our service in 2016 by increasing volume of a year of evolution, asymptomatic, and with principles of tooth mobility in left side of the jaw. Intraoral examination shows increase in volume in mandibular region with increased cortical expansion which involves teeth 36 to 41, asymptomatic to palpation or percussion of teeth involved.